Corruption Of Law Enforcement On E–KTP By Members Of The Legislature Efforts And Non Penal Criminal Policy In Perspective - Ivan; Panggabean, Mompang L; Pandiangan, Hendri Jayadi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2021)
Abstract: The crime of corruption in Indonesia is already in a very serious position and is deeply rooted in every aspect of the life of the nation and state. Corruption practices carried out by government officials have never gone down even more massive and structured as well as with very mature planning to rob the state’s money. State officials who commit criminal acts of corruption are also very smart and sophisticated to protect their crimes from being chased and even arrested by the authorities, they even collaborate with other officials to smooth the budget that will be corrupted. One of the institutions that commit the most corruption is the House of Representatives of the Republic of Indonesia (DPR-RI), where in the period from 2004-2019 it was recorded that there were 70 members of the DRP Legislature who were involved in corruption cases in various fields within the commission that was part of the task. they. One member of the House of Representatives (DPR) who became the Chairman of the DPR for the 2014-2019 period, one that was phenomenal, was that of Setya Novanto which resulted in a loss of state money of Rp. 1.2. trillion, it is really fantastic what Setya Novanto has done by involving many other members of the DPR as well as BUMN officials and finance officials to smooth the budget that he will corrupt, in corruption for the E-KTP project. Beyond common sense and conscience as a representative of the people who should be at the forefront in eradicating corruption in Indonesia. Keywords: Law Enforcement, Corruption Crimes, Non-Penal Efforts, Criminal Policy Perspective